Udayana University: Proposal for The Establishment of a ‘Political Parties and Local Governments Studies Center’ - Zuryani, Nazrina; Ali Azhar, Muhammad; Irviantono, Tedi (Udayana Journal of Social Sciences and Humanities; Vol 2 No 1 (2018): UJoSSH, Feburary 2018DO - 10.24843/UJoSSH.2018.v02.i01.p07, 2018)
In Bali, where political life is largely determined by tradition and the role of Sukarno, the main challenge is to create a cadre system unrelated to mass organizations (gangs), to oligarchy links and to traditional networks (puri/local rulers and Sukarno affiliations). To coin Riswandha Imawan?s words, there is “cadre confusion” in that the existing cadres tend not to hee d the goals of the 1998 Movement: they neglect their working duties, fail to pay taxes and do not care about political education -all things mandatory in a democracy. Aware of these failings, Academics from FISIP Udayana University, later supported by colleagues from Warmadewa University and the University of National Education, and by AIPI Bali and several women NGOs, proposed to set up a center for political parties and local Government, which would work with Udayana University’s revitalized Tax Center (different from the website Imissu at Udayana University information technology service). In the hope of getting support from the political parties cadres, the FISIP Udayana undertook a series of Focus Group Discussions of cadres followed by a survey. But the cadres refused the ?political clinic? proposed by FISIP as part of the project implementation. A new solution is now put forward by the research team: through the IbIKK (Ipteks bagi Inovatif Kreativitas Kampus), the FISIP Udayana simply proposes to revitalize the Tax Center and to Establish a Political Parties and Local Government Studies Center annexed to the Institute for Peace and Democracy/IPD at Udayana University in Denpasar.